Comparison of Seismic Parameter in RC Building using NBC 105:2020, IS 1893:2016 and ASCE 7-22 - Khatri, Abhinesh; Chaisir, Gokaran Singh; Yadav, Amit Kumar; Sah, Gautam Kumar; Chaulagain, Kishor; Khanal, Navraj; Ojha, Bimal (International Journal on Engineering Technology, 2025)
This study presents a comparative evaluation of seismic response parameters of reinforced concrete (RC) buildings analyzed according to three major seismic design codes: NBC 105:2020 (Nepal), IS 1893 (Part 1):2016 (India), and ASCE 7-22 (USA). Five RC building models ranging from G+2 to G+6 storeys, representing typical low- to medium-rise structures in Nepal, were modeled and analyzed using ETABS. The seismic parameters compared include fundamental time period, base shear, and lateral displacement.Results indicate that the fundamental time period values predicted by NBC 105:2020 are consistently higher than those obtained from IS 1893:2016 and ASCE 7-22, with an average difference of about 20–25% and 15–20%, respectively. The base shear calculated using NBC 105:2020 (at ULS condition) is the highest among the three codes, followed by ASCE 7-22 and IS 1893:2016. The difference in base shear between NBC 105:2020 and IS 1893:2016 ranges from 45% to 78%, while NBC 105:2020 and ASCE 7-22 differ by approximately 5–10%, with discrepancies becoming more pronounced for taller buildings.Similarly, NBC 105:2020 predicts the highest lateral displacements in both X and Y directions, followed by ASCE 7-22, with IS 1893:2016 yielding the lowest. The average displacement difference between NBC 105:2020 and IS 1893:2016 is 35–60%, while the difference between NBC 105:2020 and ASCE 7-22 is 10–20%. This trend suggests that NBC 105:2020 adopts a more conservative approach, potentially leading to safer yet costlier designs.The comparative analysis demonstrates that NBC 105:2020 generally prescribes more conservative seismic demands across all response parameters, aligning closely with ASCE 7-22 in design philosophy, while IS 1893:2016 tends to provide comparatively lower seismic demands. These findings emphasize the importance of adopting code provisions that balance safety, economy, and regional seismicity. The results are in good agreement with recent studies conducted on Nepalese RC buildings, confirming that NBC 105:2020 yields higher response parameters than previous versions and other regional codes.